Germanium antimony lateral nanowire phase change memory by chemical vapor deposition. Issue 5 (26th April 2013) - Gholipour, Behrad; Huang, Chung‐Che; Ou, Jun‐Yu; Hewak, Daniel W.
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> The phase change technology behind the current rewritable optical disks and the latest generation of electronic memories has provided clear commercial and technological advances for the field of data storage; by virtue of the many key attributes chalcogenide materials offer. In this work, germanium antimony (Ge–Sb) lateral nanowire phase change memory devices have been fabricated from thin films deposited by chemical vapor deposition (CVD). Deposition takes place at atmospheric pressure using metal chloride precursors at reaction temperatures between 750 and 875 °C. The fabricated devices have been characterized electrically demonstrating reversible phase change, while a lowering in power consumption in these memory cells is observed with scaling of the geometry of the nanowire cells. The results are investigated by electrothermal modeling to understand the temperature of the devices during operation. These prototype CVD‐grown Ge–Sb lateral nanowire devices show promise for applications such as phase‐change memory and optical, electronic, and plasmonic switching. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Artistic impression of Ge–Sb nanowire memory device.